Design of a Traditional Cake Recipe Book from Bangka Belitung - Vanessa, Clarysa Ceshsa; Kosasi, Anjelie Aurelia; Herli, Lyvia Clarissa; Yulius, Kevin Gustian; Situmorang, Jimmy Muller Hasoloan (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to minimize the impact of globalization on contemporary culinary preferences, document the region’s traditional snacks, and raise awareness about the importance of preserving traditional culinary practices through digital platforms. Through interviews, the research focuses on the development, testing, and refinement of traditional cakes recipes from Bangka Belitung that are on the verge of extinction due to modernization. The study seeks to produce flavors, textures, and presentations that align with local tastes by using appropriate ingredients and processing techniques. Additionally, this research results in a recipe book that serves not only as a cooking guide but also as a means of preserving culinary culture. The recipe book combines the philosophy, cultural values, and historical background of each dish, offering comprehensive insights into the gastronomic diversity of Bangka Belitung. By involving local communities and culinary experts, this study contributes to the sustainability of traditional culinary heritage through documentation and promotion to the public.